Framing Use of Force: An Analysis of News Organizations' Social Media Posts About Police Shootings. (June 2019) - Ash, Erin; Xu, Yiwei; Jenkins, Alexandria; Kumanyika, Chenjerai
This research is a systematic investigation of reporting on police use of force incidents by news organizations through social media. A sample of Tweets and Facebook posts appearing on the social media accounts of top news outlets ( N = 500) over the course of a year were analyzed. Rationalizations for use of force, characterizations of police and victims, and contextual framing were examined. Results revealed medium-based differences in challenging police actions as well as demonstrated the limitations of short-form social media in communicating news on complex issues. Implications of these findings for theory and journalistic practice are discussed.